A STUDY OF ECONOMIC, SOCIAL, AND INSTITUTIONAL FACTORS AFFECTING THE ADOPTION OF THE HIGH-RANK WHEAT SEEDS - Eskander. H. Ali; D. A. Abu Duaila; M. KH. Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The aim of this research is to investigate the effect of economic, social and institutional factors on adoption within the national program for the propagation of high-rank seeds of wheat crop. 170 questionnaires were collected, 50% of them were participants in the program from Wasit and Babil governorates. Probabilistic regression models were used to know this effect, and the possibility of adopting Farmers of improved seeds produced from the national program for the multiplication of seeds of higher grades using the (ADOPT) program. The adoption rate was 0.12%, and the total number of adopters were 12 farmers, at a rate of 14.2%. Tobit model was estimated to find out the impact of the profitability of the dunum, capital, farm size, education, type of tenure, and the number of adoption cycles expressed by 1 in the case of adoption and 0 otherwise. It was found that the increase in the size of the farm and the profitability of the dunum by one unit, the probability of adoption will increase by 5.6 and 2.3, respectively. The results of the ADOPT analysis showed that after the first (5) passes after the launch of the program’s seeds and the farmers’ knowledge of its existence, the adoption rate is expected to reach about (90.9%) of farmers, and reaching the top of adoption, which reaches about (95%) of farmers, requires a period up to about (7.4) years. The size of the initial cost of the investment in relation to the potential annual returns from the use of the technology: The size of the initial investment is (low) cost, the seeds produced from the program had a lower cost than the imported seeds and are competitive with them in quality, purity, and desirable genetic characteristics , so the cost the initial investment for these seeds is small compared to the expected return from the seed output.